2015
DOI: 10.1002/gcc.22252
|View full text |Cite
|
Sign up to set email alerts
|

Unique clonal relationship between T‐cell acute lymphoblastic leukemia and subsequent Langerhans cell histiocytosis with TCR rearrangement and NOTCH1 mutation

Abstract: Acute lymphoblastic leukemia (ALL) occasionally develops before or after the onset of Langerhans cell histiocytosis (LCH). The mechanism of LCH developing after ALL remains unclear; thus the clonality of LCH developing during maintenance chemotherapy for T-cell ALL (T-ALL) was investigated. The T-ALL and LCH cells tested had the same T-cell receptor (TCR) gamma rearrangement. Mutation analysis of the NOTCH1 gene revealed 7213C>T (Q2405X) in exon 34 in T-ALL and LCH cells, but 5156T>C (I1719T) in exon 27 only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For example, in Case 1, the MAP2K1 and RAF1 mutations were (presumably) only present in the HS and not in the CMML, suggesting that these mutations may have contributed to the development of the HS from a common KRAS mutated HSPC or primary CMML clone. Similar situations of one or more shared genetic alterations and additional unique mutations in the histiocytic neoplasm and/or associated haematological malignancy have been reported in other cases [15,18,23,25–27,29,31,32,39,41,44,45,47,52–57,59,60,63–67,87–95]. The histiocytic neoplasms often harboured unique mutations in genes encoding proteins of the MAPK signalling pathway, including NRAS [52,55], KRAS [39,53,56], BRAF [15,23,44,45,54,92,94] and RAF1 [32], again demonstrating the importance of constitutive MAPK pathway activation in the pathogenesis of the histiocytic neoplasms [3,96].…”
Section: Discussionmentioning
confidence: 67%
“…For example, in Case 1, the MAP2K1 and RAF1 mutations were (presumably) only present in the HS and not in the CMML, suggesting that these mutations may have contributed to the development of the HS from a common KRAS mutated HSPC or primary CMML clone. Similar situations of one or more shared genetic alterations and additional unique mutations in the histiocytic neoplasm and/or associated haematological malignancy have been reported in other cases [15,18,23,25–27,29,31,32,39,41,44,45,47,52–57,59,60,63–67,87–95]. The histiocytic neoplasms often harboured unique mutations in genes encoding proteins of the MAPK signalling pathway, including NRAS [52,55], KRAS [39,53,56], BRAF [15,23,44,45,54,92,94] and RAF1 [32], again demonstrating the importance of constitutive MAPK pathway activation in the pathogenesis of the histiocytic neoplasms [3,96].…”
Section: Discussionmentioning
confidence: 67%
“…One T‐ALL case (TALL023) developed Langerhans cell histiocytosis (LCH) after achieving complete remission. In this case, the LCH cells are not only a derivative of the same ancestral clone but should be a branched clone from the one that already gave rise to T‐ALL, because the LCH cells have the same TCR rearrangements (Figure D,E) . WXS was performed at an average coverage of 107.8× (range: 66.2‐201.9) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors identified two mutations in the NOTCH1 gene as well as a rearrangement in the T‐cell receptor in the T‐ALL and LCH cells. The identification of these mutations and rearrangements suggests a common clonal origin between acute leukemia and LCH 9 . An additional case of LCH following T‐ALL was also reported with an activating mutation in the NOTCH1 gene 7 …”
Section: Discussionmentioning
confidence: 97%
“…In the case of a 7-year-old male child from Japan, between acute leukemia and LCH. 9 An additional case of LCH following T-ALL was also reported with an activating mutation in the NOTCH1 gene. 7 The role of NOTCH1 in our patient and LCH has not been clearly identified but is being investigated.…”
Section: Discussionmentioning
confidence: 99%